Улус Джучи (1207-1502). Заметки о культуре Дешт-и Кыпчак в эпоху Чингисидов - Крамаровский, М.Г. (Степи Европы в эпоху средневековья, 2008)
The paper is devoted to the problem of Dasht-i Qıpčaq cultural development during the Mongolian epoch. The author suggests a three stage development model. The early Juchid period (1207 – 1250s) is actually the period of the Chingizid empire formation. Distinguishing of the early stage can hardly be overestimated for understanding cultural heritage of the first generations of the Juchids who promoted formation of the Golden Horde culture itself. In the middle Golden Horde period (the 2nd half of the 13th – the first two thirds of the 14th c.) in connection with an increasing Islamic influence at the turn of the 13th-14th centuries the time of neglecting the values of the Juchid state founders’ generation began. During the late Golden Horde period (1340s-60s – the 15th c.), when the town vector in the Juchids culture appears to be subordinated to Islamic values solely, the Turkic pre-Islamic layer in spiritual culture is still alive. This can be seen on the example of the late belt garnitures with the dragon theme.